Analisis Korelasi Antara Keberadaan Bank Syariah dan Tingkat Kesadaran Masyarakat Terhadap Produk Perbankan Syariah - Aliyyah Mahdiyyah; Haerunnisa; Ummul Haer; Kamaruddin Arsyad (STIS DAFA MATARAM, 2025)
This study aims to examine the influence of the presence of Islamic banks on public awareness of Islamic banking products in Indonesia. Data was collected through a survey involving 500 respondents from various provinces in Indonesia, using a stratified random sampling technique. The instrument used was a questionnaire measuring public perception of the presence of Islamic banks, digital services, and educational programs. Data analysis was conducted using Pearson correlation, multiple linear regression, and classical assumption tests. The results show a significant positive relationship between the presence of Islamic banks and public awareness of Islamic banking products. The presence of bank branches, access to digital services, and better educational programs can enhance public awareness. This study provides valuable insights for the development of Islamic banking strategies to expand outreach and improve public understanding of Islamic banking products.